A Aktivitas Antioksidan Dan Evaluasi Fisik Sediaan Gel Ekstrak Daun Pegagan (Centella Asiatica (L.) Urban) Sebagai Anti Aging - Permatasari, Dhea Indah; Audina, Mia; Aryzki, Saftia (LPPM Universitas Sari Mulia, 2023)
Background: Excessive exposure to sunlight can cause damage to the skin and accelerate the aging process. Therefore, the use of natural antioxidants from plants, such as pegaganleaves, in the form of a gel, can be a solution to protect the skin from damage caused by sun exposure and free radicals. Objective: Understanding the influence of varying concentrations of pegagan leaf extract (Centella asiatica (L.) Urban) on the physical evaluation and antioxidant activity of an anti-aging gel formulation. Methods: This study employed a laboratory experimental method called the one-shot case study. A gel formulation was created with variations in concentrations of pegaganleaf extract as the active ingredient, namely 5%, 10%, and 15%. Results: The influence of variations in concentrations of pegaganleaf extract (Centella asiatica (L.) Urban) on the physical evaluation of the gel, including pH testing, and the antioxidant activity in the gel formulation is highly significant. Conclusion: The research results indicate that variations in the concentration of ethanol extract from pegaganleaves in the anti-aging gel formulation affect the physical evaluation results in terms of pH testing. These variations in the concentration of ethanol extract from pegagan in the anti-aging gel formulation also impact the antioxidant activity results.